2004
DOI: 10.1111/j.1601-5223.1995.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the A and C Genomes of Brassica Campestrisand B. Alboglabra

Abstract: Meiosis was studied in pollen mother cells of two Brassica cumpestris (AA) and one B. alboglabru (CC) accessions, their resynthesized B. napus amphidiploids (AACC), and digenomic hybrids produced (AAC). The two parental species exhibited different chromatin condensation patterns at diakinesis, which enabled the differentiation between genomes and the detection of auto-and allosyndesis in the amphidiploids and digenomic hybrids. Corresponding chromatin condensation differences were manifested at mitotic prometa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 81 publications
4
12
0
Order By: Relevance
“…The occurrence of high number of univalents and multivalents, including rarely documented penta-, hexa-, and heptavalents in resynthesized B. napus reported here was in agreement with previous observations by Heneen et al (1995), indicating high degree of homoeologous pairing as a result of intragenomic duplications or the archaic homoeology of A/C genomes (Prakash and Hinata 1980). Chromosome rearrangements arising from homoeologous recombination were suggested to be the main reason for the genetic changes observed in the newly synthesized allopolyploids (Song et al 1995;Gaeta et al 2007).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The occurrence of high number of univalents and multivalents, including rarely documented penta-, hexa-, and heptavalents in resynthesized B. napus reported here was in agreement with previous observations by Heneen et al (1995), indicating high degree of homoeologous pairing as a result of intragenomic duplications or the archaic homoeology of A/C genomes (Prakash and Hinata 1980). Chromosome rearrangements arising from homoeologous recombination were suggested to be the main reason for the genetic changes observed in the newly synthesized allopolyploids (Song et al 1995;Gaeta et al 2007).…”
Section: Discussionsupporting
confidence: 94%
“…Inomata (1980) observed 0-1 trivalent and 0-1 quadrivalent while Sarashima (1973), Prakash and Raut (1983) found a maximum of two trivalents and three quadrivalents. Heneen et al (1995) documented much higher numbers of univalents ranging up to 9, as well as the rare occurrence of penta-, hexa-, and heptavalents. Chromosome bridges, fragments and lagging were also reported by Song et al (1993) and Heneen et al (1995).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…napus through homeologous recombination between A, C and R genomes is eminently possible. Several cytological studies have shown high frequency of homologous chromosome pairing among C subgenomes of Brassica species [14, 30, 38]. Our results showed that the C subgenomes in Brassicoraphanus (RRCC, 2n = 36) and B .…”
Section: Discussionsupporting
confidence: 56%
“…in U's triangle (Nagaharu, 1935) is yellow, although some white-flowered varieties exist in subspecies of the B. oleracea cytodeme. White flower has been reported in rapeseed lines resynthesized through interspecific hybridization between B. rapa and white-flowered B. oleracea (Chen et al, 1988;Heneen et al, 1995;Zhang et al, 2002). Genetic analysis of flower colour in Brassica has been conducted since 1929 (Pearson, 1929), and has been shown to be controlled by a single nuclear gene in Brassica species containing the C genome or subgenomes, with white colour dominant over yellow (Pearson, 1929;Zhang et al, 2002;Liu et al, 2004;Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%